Perlindungan Hukum Terhadap Konsumen Pada Transaksi E-Commerce Melalui Pembayaran Cash On Delivery - Putri, Shifa Nurdila; Hasmiati, Rahmatullah Ayu (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
This study aims to analyze the legal protection of consumers in e-commerce transactions with the Cash On Delivery (COD) payment method in Samarinda City. The focus of the research includes consumer legal protection according to Law Number 8 of 1999 concerning Consumer Protection and Law Number 11 of 2008 concerning Information and Electronic Transactions, the effectiveness of legal protection, and obstacles in the implementation of consumer protection. The research method used is empirical juridical with an analytical descriptive approach and data collection techniques through interviews, observations, and questionnaires distributed to e-commerce consumers in Samarinda City. The results of the study show that the existing legal protection is not fully effective because there are still various obstacles, such as low consumer awareness of their rights and weak law enforcement against irresponsible business actors. The Borneo Non-Governmental Consumer Protection Agency, the Samarinda City Police, and SPX Express have an important role in handling consumer disputes. It was found that consumers often suffer losses due to non-conforming or damaged goods, as well as difficulties in the process of returning goods and refunds. This study recommends improving consumer education, strengthening regulations related to COD transactions, and improving coordination between relevant institutions in handling consumer complaints.